KEHIDUPAN WAYANG GOLEK MENAK KEBUMEN PADA MASA KI SINDHU JOTARYONO (1955-1980) - Sunarto Sindhu (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
An article entitled the life of wayang golèk ménak Kebumen on the age of Ki Sindhu Jotaryono from 1955 to 1980 discussed about the existence of Ki Sindhu Jotaryono in developing and improving the wayang golèk ménak Kebumen play. The problems which will be investigated were: How was the history of puppeteer in Kebumen? How was the life of wayang golèk ménak Kebumen on the age of Ki Sindhu Jotaryono? Why did the play of wayang golèk ménak Kebumen decrease and what methods used to preserve and to make the ply of wayang golek Kebumen stay alive. The purpose of the investigation was to describe the history of the puppeteer of wayang golèk ménak Kebumen, the life of wayang golèk ménak Kebumen on the age of Ki Sindhu Jotaryono, the reason why the play of wayang golèk ménak Kebumen decreased, and the methods used to preserve the life of wayang golèk ménak Kebumen. Based on the analysis, the result was that on the age of Ki Sindhu Jotaryono, the play of wayang golèk ménak Kebumen improved significantly. Ki Sindhu Jotaryono created many marionettes and new characters. The decrease of the play of wayang golèk ménak Kebumen was caused by many things. It was caused by the process of globalization and the internal factor, the puppeteers. The preservation effort was conducted by improving the self of the puppeteers and of the related institutions to concern more on the life of wayang golèk ménak Kebumen. Keywords: dalang, wayang golèk ménak Kebumen, preservation